The Effect of Sensory-Motor Training on Visual Perception Skills and Attention in 8- and 9-Year- Old Students with Slow and Normal Handwriting Speed in Hamedan - Suri, Masoumeh; Azadian, Elaheh (Journal of Clinical Physiotherapy Research, 2023)
Introduction: The aim of this study was to evaluate the effect of sensory-motor training on visual perception skills and attention of 8- and 9-year-old students with slow and normal handwriting speed in the city of Hamedan. Materials and Methods: This study was a quasi-experimental study with a pre- and post-test design. Fourteen slow hand writers (I) and 30 normal hand writers were selected using a purposeful sampling method. Normal hand writers were randomly divided into experimental (II) and control (III) groups. The two experimental groups (I, II) participated in sensory-motor training with emphasized visual perception (16 sessions of 45 minutes) and the control group performed the normal school activities. All participants underwent the Stroop color test and Frostig Visual-Perceptual before and after the training. Results: Frostig and Stroop scores increased significantly in both training groups I and II (P<0.05). Writing speed increased in both experimental groups, but only in third grade students of group II was there a significant increase (P<0.05). Conclusion: Sensory-motor training increased visual perception and attention abilities in second- and third-grade elementary school students. Therefore, it can be concluded that increasing the ability to perceive vision and attention can affect the performance of fine skills such as writing.